PARTNER STANDARDIZATION IN THE TIKTOK ERA: AN ISLAMIC LEGAL CRITIQUE OF LOVE'S REDUCTION TO DIGITAL AESTHETICS - Said, Hasani Ahmad; Syarifudin, Aip; Al Faruq, Abdillah Achmad; Achmad, Adang Darmawan; Qotadah, Hudzaifah Achmad (Asosiasi Dosen Perguruan Tinggi Islam, 2025)
In the modern digital world, TikTok has proved to be a formidable medium that not just entertains but also influences culture, perceptions of love, and romantic relationships. One of the main trends is the rise of standardized partners, in which ideas of companionship are increasingly built and judged through repetitive visual conventions, aesthetic criteria, and performance displays circulating on the site. This trend tends to simplify the meaning of love into surface-level terms that emphasize physical appearance, consumer symbols, and viral trends at the expense of the deeper aspects of affection, ethical commitment, and religious compatibility. This reductionism has profound consequences for youth, as it may create unattainable expectations, promote instability, and legitimize a culture of comparison that invalidates the authenticity of emotions. From the perspective of Islamic legal commentary, such developments call for serious thought. Islamic legal classics, such as the Qur'an and Prophetic traditions, prioritize moral excellence, religious piety, compatibility, and mutual respect as the core pillars for choosing a partner and marital stability. Prioritizing the aims of online aesthetics over such timeless values constitutes a marked shift away from Islamic values that aim to conserve human dignity and to advocate for a healthy family life that lasts. Through a qualitative and normative legal analysis, this paper explores the discord between TikTok-driven criteria for partner selection and the Islamic legal framework's principles of morality, religiousness, compatibility, and mutual respect. This study employs a normative qualitative (library) research approach under Islamic law and analyzes descriptively. The study finds that although TikTok facilitates a remaking of how people imagine love, it paradoxically renders the institution of marriage a trivial matter by turning the chosen ones into image commodities for consumption. Thus, this study highlights the need to shift the criteria for selecting a partner towards values that incorporate religion, morality, and deeper emotional realities, to augment the equilibrium between the trends of online culture on the one hand and the lofty goals of Islamic legal thought on the other.